Building Self-Love in Teenagers - Fahrurrozi, A.M.; Khairat, Imalatul; Syaputra, Yogi Damai Syaputra; Septiadi, Mi’roz (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Teenagers are known to not be able to control their minds, which causes stress for many of them. Teenagers are at an age that is very vulnerable to suicide, so this problem then becomes very serious. This research aims to determine self-love in adolescents. This research uses qualitative methods and literature research. The results of this research show that building Self Love in teenagers is very important, because if someone has instilled Self Love in themselves they can accept, appreciate, and love themselves more. Meanwhile, if individuals have not instilled self-love in themselves, they will experience unhealthy mental health, punish themselves with negative comments, and continue with depression which can lead to suicide.